Handbook of research on applied intelligence for health and clinical informatics - Thakare, Anuradha, 1978-; Wagh, Sanjeev; Bhende, Manisha, 1977-; Anetr, Ahmed, 1974-; Gao, Xiao-Zhi, 1972- (Medical Information Science Reference, 2021)
"This book focuses on the study of resources and methods for the management of healthcare infrastructure and information highlighting health and clinical data structure, behavior, and interactions of natural and engineered computational systems to helps researchers and practitioners learn further investigation and solutions"--